GENERAL INSIGHT INTO COMPOSITE MATERIALS IN SCIENCE - Vasilatxon Abdullaeva Yuldashali kizi; Rakhmonov Zaylobiddin Obbosbek ugli (Academia One Publishing, 2024)
The article discusses the core ideas of origins of composite materials, new ways of obtaining them to use in mechanical engineering and physical treatments to broaden scope of their application in today’s world. The results of this theoretical analysis, in particular, are intended to give main insight into composite materials for students, studying in material science and business people who are having desires to introduce composite materials at the minimum low cost by taking necessary treatments in the condition of laboratory in Uzbekistan
Keywords: traditional materials; manufacturing processes; fracture resistant